The Jazz and blues lover's guide to the U.S. : With morethan 900 hot clubs, cooljoins, landmarks and legends, from boogie-woogie to bob and beyond - Bird, Cristiane (Addison Wesley, 1994)
ix, 434 p. : il.; 20 cm.